Does continued participation in STEM enrichment and enhancement activities affect school maths attainment?. (2nd January 2017) - Banerjee, Pallavi Amitava
Abstract: Science, technology, engineering, and mathematics (STEM) skills are very valuable for economic growth. However, the number of young people pursuing STEM learning trajectories in the United Kingdom was lower than the predicted demand during the last decade. Several STEM enrichment and enhancement activities were thus funded by the government, private, and charitable organisations to improve understanding of and raise pupil interest in these subjects. One possible way of measuring the impact of these activities in supporting pupil understanding of maths was to track the proportion of young people obtaining a 'good' grade in standardised national tests such as the GCSEs. Attainment is of course only one possible outcome of education but certainly a very important one because students are more likely to continue studying subjects in which they score higher. This makes maths attainment even more important as it is a pre-requisite for admission to STEM degree courses. This longitudinal study makes use of the National Pupil Database to assess the impact of these schemes on maths attainment of participating schools. Following up 300 intervention schools for five years the study shows the intervention group did not do any better than the comparator. The paper suggests further directions for research and offers recommendations for practice.